Current Sampling Methods for Gut Microbiota: A Call for More Precise Devices - Tang, Qiang; Jin, Ge; Wang, Gang; Liu, Tianyu; Liu, Xiang; Wang, Bangmao; Cao, Hailong (Frontiers in Cellular and Infection Microbiology, 2020)
The development of next-generation sequencing technology enables researchers to explore and understand the gut microbiome from a broader and deeper perspective. However, the results of different studies on gut microbiota are highly variable even in the same disease, which make it difficult to guide clinical diagnosis and treatment. The ideal sampling method should be less invasive, no cross-contamination, no bowel preparation, and can collect gut microbiota at different sites. In the current status, the sequencing technologies are usually based on the samples collected from feces, mucosal biopsy and intestinal fluid, etc. However, different parts of gastrointestinal tract possess various physiological characteristics which are essential for particular species of microbiota living. What's more, current sampling methods are more or less defective. For example, fecal samples are just proxy for intestinal microbiota, while biopsies are invasive for patients and not suitable for healthy controls. In this review, we summarized the current sampling methods and their advantages and shortcomings. New sampling technologies, such as Brisbane Aseptic Biopsy Device and intelligent capsule, were also mentioned in order to call for the inspiration of developing future precise description method of gut microbiome.